Mitochondrial reactive oxygen species (ROS) as signaling molecules of intracellular pathways triggered by the cardiac renin-angiotensin II-aldosterone system (RAAS) - De Giusti, Verónica C.; Caldiz, Claudia I.; Ennis, Irene L.; Pérez, Néstor G.; Cingolani, Horacio E.; Aiello, Ernesto A. (Frontiers in Physiology, 2013)
Mitochondria represent major sources of basal reactive oxygen species (ROS) production of the cardiomyocyte. The role of ROS as signalling molecules that mediate different intracellular pathways has gained increasing interest among physiologists in the last years. In our lab, we have been studying the participation of mitochondrial ROS in the intracellular pathways triggered by the renin-angiotensin II-aldosterone system (RAAS) in the myocardium during the past few years. We have demonstrated that acute activation of cardiac RAAS induces mitochondrial ATP-dependent potassium channel (mitoKATP) opening with the consequent enhanced production of mitochondrial ROS. These oxidant molecules, in turn, activate membrane transporters, as sodium/hydrogen exchanger (NHE-1) and sodium/bicarbonate cotransporter (NBC) via the stimulation of the ROS-sensitive MAPK cascade. The stimulation of such effectors leads to an increase in cardiac contractility. In addition, it is feasible to suggest that a sustained enhanced production of mitochondrial ROS induced by chronic cardiac RAAS, and hence, chronic NHE-1 and NBC stimulation, would also result in the development of cardiac hypertrophy.